2018
DOI: 10.1016/j.gaitpost.2018.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary concurrent validity of the Fitbit-Zip and ActiGraph activity monitors for measuring steps in people with polymyalgia rheumatica

Abstract: Our preliminary results suggest that in controlled conditions, the Fitbit-Zip fairly accurately measures step-count during walking in people with PMR receiving treatment. However, device error was greater than data published in healthy people. The ActiGraph may not be recommended without activation of the LFE. We identified clinical and gait-related factors associated with higher levels of functional impairment that reduced device accuracy. Further work is required to evaluate the validity of the activity moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Activity monitoring devices such as Fitbit provide the user with feedback about their level activity and progress, and present an opportunity to actively reinforce the patient in incremental quota-based gains tailored to each patient’s ability, thereby facilitating physical activity 20. Such devices are showing promising use in patients with chronic illness,21,22 including initial reports of effectiveness among patients with chronic pain 23,24. Our guiding hypothesis is that the most effective and efficient way to sustainably increase emotional and physical function among chronic pain patients is by 1) gradual and quota contingent increases in activity (walking) paired with re-engagement in activities of daily living; 2) monitoring and reinforcing quota contingent activity goals (number of steps) with a digital activity monitoring device (Fitbit)), and 3) teaching mind-body skills to manage pain, and target barriers to engaging in physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Activity monitoring devices such as Fitbit provide the user with feedback about their level activity and progress, and present an opportunity to actively reinforce the patient in incremental quota-based gains tailored to each patient’s ability, thereby facilitating physical activity 20. Such devices are showing promising use in patients with chronic illness,21,22 including initial reports of effectiveness among patients with chronic pain 23,24. Our guiding hypothesis is that the most effective and efficient way to sustainably increase emotional and physical function among chronic pain patients is by 1) gradual and quota contingent increases in activity (walking) paired with re-engagement in activities of daily living; 2) monitoring and reinforcing quota contingent activity goals (number of steps) with a digital activity monitoring device (Fitbit)), and 3) teaching mind-body skills to manage pain, and target barriers to engaging in physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…The Actigraph GT3X (Actigraph LLC, Penascola, FL, USA) represents the epitome of scientific accelerometers as it is unobtrusive, low-cost, and its sensitive triaxial accelerometers are capable of storing high-resolution, raw, unfiltered acceleration signals over long durations. The Actigraph monitor has been extensively studied in many situations: the validity for the evaluation of PA in healthy or pathological populations and the comparison with other AT (1317); used as a gold standard in some studies (18, 19). Despite all these studies, the recent systematic review by Migueles et al (20) conclude that it is necessary to take a cautious approach regarding the accuracy/reliability of Actigraph in estimating the SC in real-life situations as a function of 1-the mainly used positions (wrist and hip) and 2- the age of the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…[54,57,58] Chandrasekar found commercial pedometers (Fitbit-Zip and ActiGraph) to be less accurate in patients with altered gait, including lower gait velocity, reduced stride length, longer double-limb support phase and greater self-reported functional impairment, than in healthy subjects. [59] Adding the ActiGraph low-frequency extension improved the accuracy of stair step counts. Gaglani et al found the Fitbit Ultra step count to be more accurate in gaitcompromised patients than the Omron Step Counter HJ-113, the New Lifestyles 2000, or the Nike Fuelband.…”
Section: Fitness-related Indicatorsmentioning
confidence: 99%